Genetic Identification of Rickettsial Isolates from Fatal Cases of Brazilian Spotted Fever and Comparison with Rickettsia rickettsii Isolates from the American Continents - Labruna, Marcelo B. (American Society for Microbiology, 2014)
Fifteen bacterial isolates from spotted fever group rickettsiosis in Brazil were genetically identified as Rickettsia rickettsii. In a phylogenetic analysis with other R. rickettsii isolates from GenBank, the Central/South American isolates showed low polymorphism and formed a clade distinct from two North American clades, with the North American clades having greater in-branch polymorphism.